Télécollaboration et formation de formateurs en langues au tutorat en ligne – Un état de l'art - Marco Cappellini (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In our article, we propose to carry out a review of the literature published over the last five years (2015-2019) on the intersection between telecollaboration and teacher education in the field of computer-assisted language learning and more specifically online tutoring. The aim of this literature review is threefold. First, by situating them in the broader framework of teacher training models for integration of ICTs, it will map the models of telecollaboration that have been put in place for the training of future foreign language teachers and tutors. Second, we will highlight the most recent research findings and relate them to each other, distinguishing between three dimensions: organisational, social, and interactional, with the latter focusing on exchanges via videoconferencing. Third, on the basis of the various studies and the tension between them, the research questions that remain to be explored will be identified.